2020
DOI: 10.3390/rs12091403
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Purple Rapeseed Leaves in the Field from UAV RGB Imagery Using Deep Learning as an Auxiliary Means for Nitrogen Stress Detection

Abstract: Crop leaf purpling is a common phenotypic change when plants are subject to some biotic and abiotic stresses during their growth. The extraction of purple leaves can monitor crop stresses as an apparent trait and meanwhile contributes to crop phenotype analysis, monitoring, and yield estimation. Due to the complexity of the field environment as well as differences in size, shape, texture, and color gradation among the leaves, purple leaf segmentation is difficult. In this study, we used a U-Net model for segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…At present, the method based on target detection is mainly used for crop plant count [ 24 , 25 , 26 ]. However, plant counting using target detection technology based on UAV images poses a great challenge due to limited spatial resolution, small object size, and complex background features [ 27 ]. Previous studies have confirmed that combining vegetation indices, plant height, canopy cover, plant density, and other multiple features can improve the yield estimation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the method based on target detection is mainly used for crop plant count [ 24 , 25 , 26 ]. However, plant counting using target detection technology based on UAV images poses a great challenge due to limited spatial resolution, small object size, and complex background features [ 27 ]. Previous studies have confirmed that combining vegetation indices, plant height, canopy cover, plant density, and other multiple features can improve the yield estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Lower altitudes result in images with finer spatial resolution, but require longer flights and demand higher computational times for image processing [35]. Therefore, evaluation of flight altitude and spatial resolution was a central point in some investigations of this SI [16,24,27,29,36], being a usual objective to resample UAV images to spatial resolutions similar to those of common satellites, e.g., 5 m of Rapideye, 10 m of Sentinel-2, and 30 m of LANDSAT, in order to study the potential of using such satellite platforms instead of UAV for specific agro-forestry goals. Thus, Iizuka et al (2019) [16] discovered that CC estimation was affected by spatial resolution and coarser resolutions showed stronger correlation with manually delineated data in an RGB orthomosaic, concluding that the satellite images could be feasible for this purpose.…”
Section: Spatial Resolution Requerimentsmentioning
confidence: 99%
“…Thus, Guo et al (2021) [29] and Ye et al (2020) [27] evaluated several pixel sizes to select the optimal resolution for mapping disease areas, yielding 0.01 m for yellow rust in wheat and a minimum of 0.5 m in the case of Fusarium wilt in banana, respectively. In addition, Zhang et al (2020) [36] explored the influence of image spatial resolution on the segmentation process prior to identify N deficiency in rapeseed fields, concluding that the optimal value by using the U-Net convolutional neural network architecture will depend on the target size and stating an appropriate patch size of 256x256 pixels in the purple rapeseed leaves.…”
Section: Spatial Resolution Requerimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohamed Kerkech et al [37] proposed a new method of grape disease detection based on the SegNet [38] architecture for visible light and infrared image segmentation to identify shadows, ground, healthy and symptomatic vines, and finally merge the segmentation obtained from visible light and infrared images to generate the whole disease map of grapes. Literature [39] , a U-Net method for pixel-level purple rapeseed segmentation was proposed to calculate the model parameters by adjusting the sample size. In the literature [40] , a new thermal imaging method was proposed to calculate the color similarity problem between unripe citrus fruits and leaves, which were prone to temperature differences between fruit and leaf surfaces because of the varying rates of temperature change between the fruit and leaf surfaces caused by water mist and to build a deep learning model based on the thermal imaging system.…”
Section: Related Workmentioning
confidence: 99%